ANALISIS PENGARUH VARIABEL KEPUASAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PENUMPANG LINTAS PENYEBERANGAN KETAPANG – LEMBAR - Riska Angga Dewi; Yenita Yenita (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
The Ketapang-Lembar crossing will begin operations in April 2021. The construction of thiscrossing is intended to reduce the Gilimanuk-Denpasar traffic density and unravel the Padang Bai-Lembar crossing density. This research uses a quantitative method where the SmartPLS 3.0 application is used as a data analysis tool. Purposive sampling was the method used to collect data, and the sample was selected based on respondents who had used border transportation services at the Ketapang-Lembar crossing so that respondents had a general understanding of how to answer the questionnaire questions. The findings show that safety variables have the strongest influence on both customer satisfaction and loyalty when compared to comfort and reliability.